PERSEPSI GURU TERHADAP KEBUTUHAN PENGEMBANGAN LKPD UNTUK MELATIH KEMAMPUAN PEMECAHAN MASALAH SISWA SMP DI BANYUASIN (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This study aims to identify teachers’ perceptions of LKPD currently used, analyze their alignment with the problem-solving framework, and determine the need for developing problem solving by LKPD. A quantitative descriptive approach with a survey design was employed involving 42 junior high school science teachers in Banyuasin Regency selected through purposive sampling. Data were collected using a structured questionnaire based on the problem-solving stages proposed by Heller and Heller and analyzed descriptively using percentages and frequency distributions. The novelty of this study lies in identifying the gap between current LKPD practices and the need for problem-solving-based LKPD development in junior high school science learning in Banyuasin Regency. The results show that the highest performance occurs at the problem-focusing stage (63.25% positive responses), while the lowest performance is found at the planning stage (46.7% positive responses). This indicates that students are relatively better in identifying and understanding initial problems but still experience significant difficulties in developing structured solution plans. In addition, 83% of teachers reported uncertainty regarding the alignment between current LKPD and the problem solving framework, while all respondents (100%) expressed the need for problem solving based LKPD development. These findings highlight a clear gap between existing instructional materials and the demands of systematic problem solving skills, providing an empirical basis for developing more structured LKPD to better support students’ physics problem solving abilities.